Locomotory system functional evalution in patients with lumbar degenerative disc disease in the preoperative period according forceplate - Алзін Ходуд, (Alzin Hodod); Колесніченко Віра Анатоліївна, (Vera Kolesnichenko) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: to study preoperatively the functional properties of the musculoskeletal system in patients with lumbar osteochondrosis with different variants of myotonic reactions. Materials and methods: protocols of clinical and biomechanical examination of 70 patients with lumbar osteochondrosis aged 27–44 years. Results: according to forseplate a statistically significant displacement of the LG projections was identified: in the sagittal plane one was shifted anteriorly in all variants of myotonic reactions, as well as in the frontal plane an asymmetric position of the LG projections in patients with expressed antalgic scoliosis was observed. Intense pain is not correlated with forceplate parameters but strongly and directly impacts on the general disability level. Conclusions: preoperatively in patients with lumbar osteochondrosis vertical posture stability in all variants of myotonic reactions was impaired.